Investigation of SrSiO3:Ce crystals for scintillator application. (28th May 2021) - Nakamura, Fumiya; Kantuptim, Prom; Nakauchi, Daisuke; Kato, Takumi; Kawaguchi, Noriaki; Yanagida, Takayuki
Abstract: We developed SrSiO3 :Ce crystals with different dopant concentrations of 0.5%, 1.0% and 2.0% using the floating zone method and investigated the scintillation and storage luminescence properties. Under X-ray irradiation, a broad emission band peaking at around 360 nm was observed in all the samples. The decay time constants were in the range of 33–34 ns, which were typical values for the 5d–4f transitions of Ce 3+ . The 1.0% and 2.0% Ce-doped samples showed a photoabsorption peak under 241 Am 59.5 keV γ -rays and the light yield was 1200 and 1400 ph MeV −1, respectively. The results of pulse-height spectra and thermally-stimulated luminescence showed a complementary relationship between scintillation and ionizing-radiation-induced storage luminescence properties in Ce-doped SrSiO3 .